HISTORIA KARDIO- I TORAKOCHIRURGIICongenital cardiac surgery. How it started… - Malec, Edward; Januszewska, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
We present the history of congenital heart surgery. Emphasis is placed on the creativity and the vision of the pioneers whose extraordinary skills and determination led to the contemporary congenital cardiac surgery, where almost all congenital defects can be anatomically or functionally corrected. The development of many important operations is reviewed and they are placed in the context of their times.